Solve for x 7(x – 9) = 8x – 6

Question

Solve for x 7(x – 9) = 8x – 6

in progress 0
2 weeks 2021-10-08T12:10:10+00:00 2 Answers 0

Answers ( )

  1. Emma
    0
    2021-10-08T12:11:15+00:00

    Answer:

    x= -57

    Step-by-step explanation:

    7x-63+8x-6

    -x-63-7

    -x=57

    x=-57

  2. Emma
    0
    2021-10-08T12:11:49+00:00

    Answer:

    x = -57

    Step-by-step explanation:

    Simplify both sides of the equation:

    Distribute:

    (7)(x) + (7)(-9) = 8x + -6

    7x + -63 = 8x -6

    7x – 63 = 8x – 6

    Subtract 8x from both sides

    7x−63−8x=8x−6−8x

    −x − 63 = −6

    Add 63 to both sides

    −x − 63 + 63 = −6 + 63

    -x = 57

    Divide both sides by -1

    -x / -1 = 57 / -1

    Therefore, you get x = -57

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )